Precision staging and management of Barrett's oesophagus and oesophageal cancer: genomic, imaging and pathological biomarkers - Findlay, John Mitchell (2016)
Barrett’s oesophagus and oesophageal cancer represent two of the most important and challenging oesophageal disease processes globally, combining increasing incidences with high morbidity treatments, often with poor clinical outcomes. A major contributory factor is that disease susceptibility, progression and response to therapy are largely unpredictable, due to inherent biological complexity and variability. At present, just staging groups are used routinely as thresholds for guiding the use of therapies such as ablation, resection, and oncological therapies. However, these represent blunt tools that do not necessarily reflect patients’ experiences, or appropriately select from the range of treatments available. The aim of this thesis was to explore the potential of genomic, imaging, and pathological biomarkers in guiding more tailored and personalised therapy.